THE EFFECT OF TEACHING USING THE "PLAN STRATEGY" ON THE ACHIEVEMENT AND ATTITUDE TOWARDS PHYSICS FOR FIRST GRADE STUDENTS - Asst Prof. Dr. Hassan Arif Abdal (American Journals Publishing, 2023)
The study aimed to find out the effect of teaching using "Plan Strategy" on the achievement and attitude towards physics among the first intermediate grade students. The research sample consisted of 60 students from the first intermediate grade students, with 30 students for the experimental group studying according to Plan Strategy, and 30 students for the control group studying according to the usual method. After the researcher made sure of the equality of the research groups, the researcher built a test achievement and adopted a measure of attitude after making sure of its validity and reliability, the researcher used the (t-test) to find out the results, and concluded that the Plan strategy has an effective effect on achievement and attitude for the experimental group compared to the control group, and the researcher suggested a number of recommendations and proposals.